A espacialização da rede bancária e sua importância na estruturação da cidade de Ourinhos (SP): uma abordagemintrodutória - Tangerino, Danilo Fávero [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In the current historical period, we see a greater evidence regarding the role of large corporations in cities, mainly working in economic sectors ratifying processes of fragmentation and spatial segregation in relation to access to the various services offered by the system itself, in this case the banking system. Within this analysis, it is important to understand the role of changes in the logical organization of cities that stand out in the urban network, which are medium-sized cities in a regional focus or mid-sized cities in microrregional scope as Ourinhos (SP), which stands out among many aspects, from the cities of its immediate microregion. The objective is to analyze, in an introductory way, the influence of banking networks, from the location of branches and service centers, in the structuring of Ourinhos as well as the spatialization of this network. Therefore, a study was made of the emergence and development of the Brazilian Financial System, addressing the importance of telecommunications to the emergence of other products, together with an analysis from other studies in the city, to understand how the banking network influences and affirms the segregation and structuring of Ourinhos / SP Keywords: banking network; social and special segregation; structuring of the city; producing agents in space.
Keywords: Geografia urbana - Ourinhos (SP); Bancos - Ourinhos (SP); Espaço urbano; Planejamento urbano